SOIL PHYSICAL PROPERTIES AND PRODUCTION OF UPLAND ULTISOL SOIL - soelaeman, yoyo; Haryati, Umi (AGRIVITA, Journal of Agricultural Science, 2012)
Acid upland soil in Indonesia has a great potential for agricultural development but the soil physical properties have been degraded. The use of manure and direct application of Gresik phosphate rock (PR) was an alternative to improve land productivity and crop yields. The objective of the study was to evaluate the effects of manure and P sources on soil physicalÂ  properties and yield of foods crop that was arranged on intensive cropping systems of upland rice + maize -/- cassava- mungbean. The experiment was carried out in Tamanbogo Station Farm, East Lampung since 2007 until 2009 using randomized complete block design with 3 replications. The treatments were (1) 10 t ha-1 manures+1 t ha-1 of PR, (2) Without manure+1 t ha-1 of PR, (3) 10 t ha-1 manures+100 kg ha-1 of SP 36, and (4) Without manure+100 kg ha-1 of SP 36. The results showed that the application of manure along with PR improved soil physical characteristics of ultisol soil and gave the highest yield of foods crops with B/C in year 3th was 3.60. Â Â